Resources for Reasoning - Brown, Paul (Mathematical Association of Victoria, 2017)
Before we teach reasoning we must confront some deeply-entrenched counter-productive human behaviours. An important one of these is 'confirmation bias', a failing which prevents us from applying logical analysis. Confirmation bias is our tendency to seek evidence in support of our beliefs, neglecting counter-examples which might cause us to re-think. Only when our students realise that psychological obstacles can be overcome will our efforts with reasoning prove fruitful. This essay presents some approaches which may assist students to address biases and apply insightful thinking.